Grooming the next generation of Muslim Researchers - Musa Abu Hassan (Universiti Sains Islam Malaysia, 2024)
The advancement of societies is dependent on the knowledge that they discover, generate, accumulate and share among the members. Knowledge does not come by it sex there should be groups of trained individuals to seek, uncover and package the knowledge to be utilized by the society for social, economic as well a spiritual advancement. History has recorded that there were many Muslim scholars who had very successfully discovered the many disciplines of knowledge that became the milestones for further research and development. This paper will discuss on why we should develop young scholars, example of two institutions working along this idea, the skills need to be acquired by the young researchers, and the support mechanisms that will expedite the development of young researchers. With the resurgence of Islam worldwide, it is more pressing to address the gap in,fulfilling the needs of the Muslim ummah with regard to overall societal development and well-being.